The Secular City : Secularization and Urbanization in Theological Perspective - Cox, Harvey Gallagher (Book collections on Project MUSE., 2013)
Since its initial publication in 1965, The Secular City has been hailed as a classic for its nuanced exploration of the relationships among the rise of urban civilization, the decline of hierarchical, institutional religion, and the place of the secular within society. Now, half a century later, this international best seller remains as relevant as when it first appeared. The book's arguments--that secularity has a positive effect on institutions, that the city can be a space where people of all faiths fulfill their potential, and that God is present in both the secular and formal religious realms-still resonate with readers of all backgrounds.